The Influence of Individual Spirituality Toward Spirit at Work in Enhancing Organizational Commitment and Job Satisfaction - Amelia Naim Indrajaya (International Journal of Business Studies, 2018)
The low spirit, lack of higher purpose and meaning in the workplace has an impact towards employees’ morale. Eventually, the commitment to moral will decrease employees’ productivity and organizational commitment at work. Therefore, this study aims to investigate the inluence of individual spirituality toward spirit at work and how it enhances job satisfaction and organizational commitment. The quantitative research through questionnaires was conducted in the branch ofice of PT. Telkom with the highest revenue in the Central of Jakarta. The indings show the importance of workplace spirituality in enhancing job satisfaction and organizational commitments as important factors in increasing company’s performance. Despite the growing belief that workplace spirituality signiicantly relates to performance, the evidence is still needed based on academically proven empirical research that great spirituality is part of the strategic management approach toward better performance. Furthermore, this study supported the hypotheses that individual spirituality is positively impacting spiritat work and in turn positively enhancing job satisfaction and organizational commitment. Further quantitative explanatory approach and/or qualitative exploratory approach will be needed to reach a more solid conclusion.